Stereotipi o reformaciji: primer odpustkov - Bjelčevič, Aleksander (Slavia Centralis, 2020)
Reformation stereotypes: the case of indulgences. Today the Reformation is of great interest to us because of its lay achievements such as literary language. We know little about its religious and theological endeavours and even this knowledge is wrong in many cases, such as the belief that Protestants denied Mary’s virginity, the existence of saints, and that indulgences are the remission of sins. In this article I explain in detail the significance of indulgences.